The tiger rising [videorecording (DVD)] - Convery, Christian, 2009-; Mills, Madalen; Trammell, Sam, 1971-; McPhee, Katharine, 1984-; Quaid, Dennis; Queen Latifah, 1970-; DiCamillo, Kate (Paramount, 2022)
The moving story of an eleven-year-old boy who finds a caged tiger in the woods behind the motel where he lives with his father. Now, the boy must decide what to do with his discovery and at the same time come to terms with his troubled past.